Deuxieme Classe . Second Class - Nguele, Gerard Desire (Nguele, Gerard Desire, 2003)
Duration: 00:26:00 After fifteen years, Cameroonian Gerard Desire Nguele returns to the train that he, as a boy, used to take with his mother when they travelled to visit Gerard's brother. The old train needs several hours to cover the 35 kilometer railroad track. Throughout this reenacted trip, the filmmaker talks to the fellow passangers, watches the women jumping onto the train directly from the bush, etc. During the journey across one of the oldesrt railroad lines in Cameroon, the director tries to reconcile himself with the recent death of his mother, an attempt to live without her and to "become a man."